The art of Strategic Leadership: How Leaders at All Levels Prepare Themselves, Their Teams, and Organizations for the Future - Stowell, Steven J. (John Wiley and Son, 2016)
The book gives you the cove values and priorities to elevate you into the strategic class of leader.